Synergism between the low-level jet and organized convection at its exit region - Saulo, Andrea Celeste (2007)
Previous studies suggest that the enhanced meridional extent of some South American low-level jet events (known as Chaco jets) is a consequence of a positive feedback between the low-level wind and strong convection that is usually observed at their exit region. To assess how this interaction takes place, a Chaco low-level jet event observed between 18 and 19 December 2002 (i.e., during the South America Low-Level Jet Experiment) and the associated mesoscale convective system that evolved at its exit region have been selected to perform numerical experiments where diabatic heating effects associated with phase changes can be quantified. This case study has also been used to analyze the diurnal oscillations related to planetary boundary layer (PBL) mechanisms in order to describe whether the observed evolution of the low-level wind can be explained either by PBL-related forcing or by the interaction with convection. The sensitivity experiments confirm that there is a positive feedback at low levels between convection and the northerly wind flow that becomes accelerated and also aids in the identification of a strong coupling between organized convection and the upper-level circulation, resulting in an increase of the upper-level jet strength downstream of the simulated precipitation area. A conceptual model of how these systems (i.e., convection, low- and upper-level jets) mutually interact is proposed, which differs from coupling mechanisms documented for the Great Plains low-level jet.